The Influence of Compensation, Work Environment, and Motivation on Employee Performance at PT. Lippo Karawaci Tbk - Susan Christiani (Priviet Social Sciences Journal, 2022)
This study aims to examine the effect of compensation, work environment, and motivation on employee performance at PT. Lippo Karawaci Tbk. A quantitative approach was employed using survey methods, with data collected from 164 respondents through structured questionnaires. Data analysis was conducted using multiple linear regression, supported by correlation analysis, classical assumption tests, and hypothesis testing. The results show that compensation, work environment, and motivation have positive and significant effects on employee performance, both partially and simultaneously. Compensation has the strongest influence, followed by the work environment and motivation. The regression analysis indicates that all independent variables contribute positively to improving employee performance. The coefficient of determination (R² = 0.696) suggests that 69.6% of the variation in employee performance can be explained by these variables, while the remaining 30.4% is influenced by other factors. These findings highlight the importance of effective compensation systems, a supportive work environment, and strong employee motivation in enhancing organizational performance. This study provides practical implications for management in developing strategies to improve employee performance through integrated human resource practices.